The effect of Facebook in stimulating cultural tourism - Azeez, Dr. Zuhier Abbas; al-waeli, Athraa sattar kadhem jaber (The journal of contemporary issues in business and government, 2021)
The modern means of communication Facebook is one of the most famous modern means of communication because of its advantage over other modern means of communication, with several advantages that made it the forefront of cyberspace. Facebook is an effective, interactive, interconnected communication medium that includes the largest human gathering on the face of the earth on its website that attracts the tourist masses using this method by promoting tourism activity, and all this is done by uploading photos, video clips, and their impressions about the places visited to promote the site of tourist attractions . Cultural tourism is a type of tourism concerned with the tourism of antiquities, heritage, folklore, and the material and intangible cultural heritage of peoples, as well as visiting museums, theaters, libraries and all cultural activities and events, and cultural tourism is an activity that covers all travel purposes where people learn about each other ways of life and follow thought, and the tourist countries have always promoted cultural tourism. Because of its growing importance in the global tourism market. To accomplish this study, a field survey method was adopted. The study concluded with many conclusions that had a role in stimulating cultural tourism in the city of Baghdad. The importance of Facebook in tourism activity is highlighted by achieving awareness of the importance of tourism in society and the formation of tourism culture among its Tourism activity depends on Facebook in providing tourism information, displaying tourism services, and introducing tourist facilities and tourist reservation